2012
DOI: 10.1016/s1734-1140(12)70924-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased concentration of metronidazole and its hydroxy metabolite in colon cancer in women

Abstract: Abstract:Background: Metronidazole (MTZ) is indicated in the prevention of infections during surgical procedures. However, some data have shown that metronidazole has carcinogenic potential. Methods: In the present work, we determined concentrations of metronidazole and its hydroxy metabolite (MTZOH) in colorectal cancer patients. MTZ and MTZOH were measured in tumor tissue and surrounding healthy tissue by LC-ESI-MS-MS method. Results: We found different concentration of MTZ and MTZOH in colorectal cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…15 Our previous study on patients with CRC showed increased accumulation of MTZ in the tumor tissue. 16 Thus, MTZ is used in colon cancer surgery; the main objective of our investigation was to verify the possible effect of MTZ on DLD-1 colon cancer cell line when the dose is repeated.…”
Section: Introductionmentioning
confidence: 99%
“…15 Our previous study on patients with CRC showed increased accumulation of MTZ in the tumor tissue. 16 Thus, MTZ is used in colon cancer surgery; the main objective of our investigation was to verify the possible effect of MTZ on DLD-1 colon cancer cell line when the dose is repeated.…”
Section: Introductionmentioning
confidence: 99%